Progress in organocatalysis with hypervalent iodine catalysts. (5th September 2022) - Singh, Fateh V.; Shetgaonkar, Samata E.; Krishnan, Manjula; Wirth, Thomas
Abstract : Hypervalent iodine compounds as environmentally friendly and relatively inexpensive reagents have properties similar to transition metals. Abstract : Hypervalent iodine compounds as environmentally friendly and relatively inexpensive reagents have properties similar to transition metals. They are employed as alternatives to transition metal catalysts in organic synthesis as mild, nontoxic, selective and recyclable catalytic reagents. Formation of C–N, C–O, C–S, C–F and C–C bonds can be seamlessly accomplished by hypervalent iodine catalysed oxidative functionalisations. The aim of this review is to highlight recent developments in the utilisation of iodine(iii ) and iodine(v ) catalysts in the synthesis of a wide range of organic compounds including chiral catalysts for stereoselective synthesis. Polymer-, magnetic nanoparticle- and metal organic framework-supported hypervalent iodine catalysts are also described.